2005
DOI: 10.1091/mbc.e05-07-0687
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Profiles of REST Interactions with Its Target Genes at Different Stages of Neuronal Development

Abstract: Differentiation of pluripotent embryonic stem (ES) cells through multipotent neural stem (NS) cells into differentiated neurons is accompanied by wholesale changes in transcriptional programs. One factor that is present at all three stages and a key to neuronal differentiation is the RE1-silencing transcription factor (REST/NRSF). Here, we have used a novel chromatin immunoprecipitation-based cloning strategy (SACHI) to identify 89 REST target genes in ES cells, embryonic hippocampal NS cells and mature hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
131
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 44 publications
10
131
0
Order By: Relevance
“…53 Two complementary studies have shown differential REST occupancy profiles in ESCs and NSCs and these findings suggested the presence of distinct and overlapping developmental REST regulons. 15,81 For example, one of these studies found 810 and 679 RE1 sites occupied by REST, respectively, in ESCs and NSCs. 15 These included only 32 unique sites in NSCs.…”
Section: Evolving Roles Of Rest and Corest In Seminal Neural Cell Fatmentioning
confidence: 99%
“…53 Two complementary studies have shown differential REST occupancy profiles in ESCs and NSCs and these findings suggested the presence of distinct and overlapping developmental REST regulons. 15,81 For example, one of these studies found 810 and 679 RE1 sites occupied by REST, respectively, in ESCs and NSCs. 15 These included only 32 unique sites in NSCs.…”
Section: Evolving Roles Of Rest and Corest In Seminal Neural Cell Fatmentioning
confidence: 99%
“…A master repressor, repressor element 1-silencing transcription factor (REST), recruits various corepressors, suppressing neuronal programs in nonneuronal lineages (1)(2)(3)(4)(5)(6)(7). REST binds to a conserved 23-bp motif, repressor element 1 (RE1), of numerous neuronal genes (8,9).…”
mentioning
confidence: 99%
“…In addition, Zuccato and colleagues demonstrated that a wild-type huntingtin protein inhibits the repressive effect of REST by sequestering it in the cytoplasm, whereas mutant huntingtin causes an aberrant nuclear accumulation of REST (14,15). Because huntingtin is also expressed in nonneuronal cells, there is an ongoing search for factors that may regulate the functionality of REST, particularly in mature neurons in the adult brain (4,16).…”
mentioning
confidence: 99%
“…REST occupies a central role in non-neuronal lineage restriction through its ability to suppress the nonspecific and premature expression of neuronal genes in non-neuronal cells and neural progenitor cells, respectively (4,5,10,11). Consistent with such a role, the expression of REST is dominantly constrained in non-neuronal and neural progenitor cells, although low levels of REST protein are maintained in some populations of postmitotic neurons, most notably those of the hippocampus (10,(12)(13)(14)(15). Functional inactivation of REST in vertebrates leads to early embryonic lethality and ectopic expression of neuronal genes in non-neuronal tissues (16), whereas its forced overexpression causes axon-pathfinding errors (17).…”
mentioning
confidence: 99%